2015
DOI: 10.1038/jp.2015.109
|View full text |Cite
|
Sign up to set email alerts
|

United States and territory policies supporting maternal and neonatal transfer: review of transport and reimbursement

Abstract: OBJECTIVE Summarize policies that support maternal and neonatal transport among states and territories. STUDY DESIGN Systematic review of publicly available, web-based information on maternal and neonatal transport for each state and territory in 2014. Information was abstracted from published rules, statutes, regulations, planning documents and program descriptions. Abstracted information was summarized within two categories: transport and reimbursement. RESULTS Sixty-eight percent of states and 25% of te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 43 publications
1
13
0
Order By: Relevance
“…Few studies have focused on interfacility transport in neonatal populations. 11,[15][16][17] In agreement with previous studies, a low GA was the most significant factor associated with adverse short-term outcomes in our cohort. Additionally, low birth weight and birth by cesarean section tended to be associated with adverse outcomes, although the differences were not statistically significant.…”
Section: Discussionsupporting
confidence: 92%
“…Few studies have focused on interfacility transport in neonatal populations. 11,[15][16][17] In agreement with previous studies, a low GA was the most significant factor associated with adverse short-term outcomes in our cohort. Additionally, low birth weight and birth by cesarean section tended to be associated with adverse outcomes, although the differences were not statistically significant.…”
Section: Discussionsupporting
confidence: 92%
“…Using a U.S. national-level data set containing 9,722 VLBW infant transfers among 2,122 hospitals, we found a variety of different types of communities, varying from highly centralized to highly regionalized. That we found strongly regionalized networks is perhaps not surprising given the financial incentives of the health care market, the differences in state regulations governing NICU expansion, and geography [3,4,10,11,12,13,6]. Our communities were largely organized around state boundaries, but 25% of communities overlapped at least four states and 8% of all transfers occurred between hospitals in different states.…”
Section: Discussionmentioning
confidence: 72%
“…To advance our understanding of top-down vs. bottom-up processes in hospital transfer networks more specifically, and complex systems more generally, an important extension of this work is to analyze how the VLBW infant transfer network structure has changed over time; in particu-lar, whether changes in state-level policies on transport or changes in reimbursement and financial incentives are associated with the types of changes in network structure predicted by our results. However, one important policy implication of the current research shows that VLBW transfers cross state borders while states policies/regulations governing maternal and neonatal transport do not [11]. The associations between existing state laws and community structure remain an important part of future research.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Transferring infants who no longer requireintensive care to community hospitals closer to home has many potential advantages, including decreased family stress, earlier involvement of primary providers, and more efficient use of resources within a care network. [20][21][22][23][24] Prior studies suggest that transfer of stable, recovering infants to lower level special care nurseries is safe and cost effective, 25,26 particularly when they will spend >1 week in the community hospital. 27 Although some cost savings may be offset by a trend toward longer length of stay in the community hospital, 26 others have shown that overall length of stay is similar to that of the referring NICU for low birth weight infants 23,28 Times of high patient volume or acuity may create the need to identify which infants have least need for high-level ICU services and would be the best candidates for retro-transfer.…”
mentioning
confidence: 99%